2007
DOI: 10.1073/pnas.0704843104
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for antiactivation in bacterial quorum sensing

Abstract: Bacteria can communicate via diffusible signal molecules they generate and release to coordinate their behavior in response to the environment. Signal molecule concentration is often proportional to bacterial population density, and when this reaches a critical concentration, reflecting a bacterial quorum, specific behaviors including virulence, symbiosis, and horizontal gene transfer are activated. Quorum-sensing regulation in many Gramnegative bacteria involves acylated homoserine lactone signals that are pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
69
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 29 publications
0
69
0
1
Order By: Relevance
“…The antiactivator protein, TraM, inhibits the DNA binding of TraR (30,31). Structures of the TraR-3OC8-HSL-TraM complex showed that TraM binds between the LBD and DBD in a symmetric configuration, making numerous contacts with DBD, LBD, and the linker between them, which places the DBDs in a position that is incompetent to bind to DNA (13,(32)(33)(34). Because TraM can form a complex with TraR while it is simultaneously bound to DNA (34), it is quite unlikely that TraR adopts a crosssubunit architecture, and indeed the linker of TraR probably evolved to bind to TraM and not necessarily to make the extensive interactions with the LBD or DBDs that have been observed in the QscR or CviR structures (16).…”
Section: Discussionmentioning
confidence: 99%
“…The antiactivator protein, TraM, inhibits the DNA binding of TraR (30,31). Structures of the TraR-3OC8-HSL-TraM complex showed that TraM binds between the LBD and DBD in a symmetric configuration, making numerous contacts with DBD, LBD, and the linker between them, which places the DBDs in a position that is incompetent to bind to DNA (13,(32)(33)(34). Because TraM can form a complex with TraR while it is simultaneously bound to DNA (34), it is quite unlikely that TraR adopts a crosssubunit architecture, and indeed the linker of TraR probably evolved to bind to TraM and not necessarily to make the extensive interactions with the LBD or DBDs that have been observed in the QscR or CviR structures (16).…”
Section: Discussionmentioning
confidence: 99%
“…Antiactivators from other systems (non-AraC targets) function by one of three mechanisms: preventing self-association of the activator (5), occluding the DNA binding domain from interacting with DNA (19,22,24), or inducing conformational changes that alter the structure of the DNA binding domain (6). ExsD inhibits ExsA-dependent transcription by employing at least two of these mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…S2:2), revealed new structural insights into TraM/TraR associations and inhibition of premature TraR activity based on the more structurally tractable TraM/TraR NGR antiactivator complex of Rhizobium sp. strain NGR234 (18). These studies provide evidence for an allosteric mechanism (Fig.…”
Section: Intercellular Communication-competence and Horizontal Gene Tmentioning
confidence: 55%